Purification and biochemical characterisation of the EcoR124 type I modification methylase. - Taylor, I (1992)
Large scale purification of the type I modification methylase EcoR124 has been achieved from an over-expressing strain by a two step procedure using ion-exchange and heparin chromatography. Pure methylase is obtained at a yield of 30 mg per gm of cell paste. Measurements of the molecular weight and subunit stoichiometry show that the enzyme is a trimeric complex of 162 kDa consisting of two subunits of HsdM (58 kDa) and one subunit of HsdS (46 kDa). The purified enzyme can methylate a DNA fragment bearing its cognate recognition sequence. Binding of the methylase to synthetic DNA fragments containing either the EcoR124 recognition sequence GAAN6RTCG, or the recognition sequence GAAN7RTCG of the related enzyme EcoR124/3, was followed by fluorescence competition assays and by gel retardation analysis. The results show that the methylase binds to its correct sequence with an affinity of the order 10(8) M-1 forming a 1:1 complex with the DNA. The affinity for the incorrect sequence, differing by an additional base pair in the non-specific spacer, is almost two orders of magnitude lower.